Revitalizing traditional villages through Bookstore-led Rural Tourism: a case study of three Bookstore villages in Rural China - Yingju Zhang; Yu Okamura (Journal of Asian Architecture and Building Engineering, 2024)
Rural tourism has been used to revitalize traditional villages by integrating creative tourism service facilities. This paper focuses on the role of physical bookstores as a significant tourism service facility in rural China. In urban settings, physical bookstores have faced numerous challenges, leading them to evolve into new forms and offer immersive experiences to visitors. Bookstores have also ventured into traditional Chinese villages that leads to rural revitalization. Despite the evidence of rural tourism initiated by bookstores, it received little attention in academia. This paper aims to propose the concept of bookstore-led rural tourism, investigates its tourism development process and impacts on rural communities. Three bookstore villages were selected as case studies and the research was conducted using qualitative and inductive approaches. The findings confirm that (1) rural bookstores play a leading role in the rural tourism development process through the three stages; (2) bookstore-led rural tourism also revitalizes traditional Chinese villages at the material, social, and spiritual levels, with rural bookstores playing a crucial role in shaping rural identity. This paper recommends that the application of bookstore-led rural tourism to revitalize traditional villages using a holistic approach should be valued in future research studies and real-life practice.